2012
DOI: 10.1371/journal.ppat.1002549
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Activation of the Adenoviral Genome Is Mediated by Capsid Protein VI

Abstract: Gene expression of DNA viruses requires nuclear import of the viral genome. Human Adenoviruses (Ads), like most DNA viruses, encode factors within early transcription units promoting their own gene expression and counteracting cellular antiviral defense mechanisms. The cellular transcriptional repressor Daxx prevents viral gene expression through the assembly of repressive chromatin remodeling complexes targeting incoming viral genomes. However, it has remained unclear how initial transcriptional activation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 74 publications
1
63
1
Order By: Relevance
“…In the current study, digoxin and digitoxin usually were added at the end of a 60-min adsorption period, by which time HAdV-C5 genome delivery is complete (50). Digoxin has been shown to increase the formation of promyelocytic leukemia (PML) bodies (51), which are known to have an antiviral function (52,53), but E1A expression in the presence of digoxin argues against inhibition by PML bodies (51-53). However, reduced uptake, genome delivery, and/or increased formation of PML bodies may have contributed to the reduction in E1A expression when cells were pretreated with drug.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, digoxin and digitoxin usually were added at the end of a 60-min adsorption period, by which time HAdV-C5 genome delivery is complete (50). Digoxin has been shown to increase the formation of promyelocytic leukemia (PML) bodies (51), which are known to have an antiviral function (52,53), but E1A expression in the presence of digoxin argues against inhibition by PML bodies (51-53). However, reduced uptake, genome delivery, and/or increased formation of PML bodies may have contributed to the reduction in E1A expression when cells were pretreated with drug.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, our group showed that the constitutive PML NB protein Daxx represses Ad5 gene expression and productive infection (80). This is counteracted by capsid protein pVI-dependent Daxx relocalization from the nuclear bodies at immediate-early times of infection, followed by E1B-55K-dependent proteasomal degradation (67,80).…”
Section: Discussionmentioning
confidence: 99%
“…For dual-luciferase assays, subconfluent H1299 cells were transfected as described above, using 1 g of reporter (pGL-C3G5-luc or pGL-E2-early promoter), 1 g of pRL-TK (Promega), which expresses Renilla luciferase under the control of the herpes simplex virus (HSV) thymidine kinase promoter, and 1 g of effector plasmids (E1A-12S, E1A-13S, PML-II, and pG4-p300). Cell extracts were prepared, measured, and normalized as described recently (67).…”
Section: Methodsmentioning
confidence: 99%
“…Human foreskin fibroblasts (HFFs) were obtained from J. Dechanet (CIRID University of Bordeaux) and maintained as described above. Recombinant replication-competent human adenovirus type 5 (Ad5), replication-deficient E1-deleted green fluorescent protein (GFP)-expressing Ad5 vector (Ad5-GFP), and Ad5-GFP-M1, in which the PPxY motif of protein VI is mutated (33), were amplified and purified as described previously (33,34). Ad infection was carried out at a multiplicity of infection (MOI) of 100 PFU/cell.…”
Section: Methodsmentioning
confidence: 99%